Disability in German-speaking Europe : history, memory, culture - Leskau, Linda, 1985-; Nusser, Tanja; Sorrels, Katherine (Studies in German literature, linguistics, and culture., 2022)
"Ableism remains the most socially acceptable form of intolerance, with pejoratives referencing disability - and intellectual disability in particular - remaining largely unquestioned among many. Yet the understanding, depiction, and representation of disability is also clearly in a process of transformation. This volume analyzes that transformation, taking a close look at attitudes toward disability, understood as a "deviation" from what a non-disabled body should ostensibly be able to do and how it should look, in historical and contemporary German-speaking contexts. The volume begins with an overview of the emergence and growth of disability studies in German-speaking Europe against the background of the field's emergence a decade or so earlier in the US and UK. The differences in timing, methodology, and research concentrations bring into focus how each cultural context has shaped the field. Building on recent scholarship that uses a cultural studies approach, the volume's three sections analyze disability and ability constructs in history, memory, and culture. The essays in the history section examine the emotions, morality, and power as they are negotiated on the individual level. Those in the memory section grapple with the origins of the Nazi persecution of people with disabilities, the fight for recognition of this genocide, and the politics of its commemoration. Finally, the culture section offers close readings of disability in literary and filmic texts from the twentieth and twenty-first centuries"--